A robotics wheelchair for crowded public environment. - Prassler, E.
Describes the robotic wheelchair MAid (Mobility Aid for Elderly and Disabled People). MAid's task is to support and transport people with limited motion skills. It is based on a commercial wheelchair that has been equipped with an intelligent control and navigation system. Conversations with disabled and elderly people and with their physicians indicate that the automatic functions desired in a robotic wheelchair do not include following walls or passing doorways, but do include navigation in narrow, cluttered environments and through wide, crowded areas. MAid performs these functions
Keywords: MAid; Mobility Aid for Elderly and Disabled People; Crowded public environment; Disabled persons; Elderly persons; Intelligent control; Narrow cluttered environments; Navigation system; Robotics wheelchair; Wide crowded areas